The effect of roasting degrees on bioactive compounds levels in Coffea arabica and their associations with glycated hemoglobin levels and kidney function in diabetic rats - Ola Al-Tamimi, Shady Helmi Awwad, Reem Issa, Talal Al-Qaisi, Husam Abazid, Ahmad Daraosheh, Beisan Mohammad, Tsvetanka Filipova, Mahmoud Abu-Samak (Journal of Applied Pharmaceutical Science, 2024)
The current study aims to assess the content of coffee oil, diterpenes, caffeine, and chlorogenic acid in coffee beans, and to evaluate the effects of roasting degrees on bioactive compound levels in Coffea arabica and their associations with glycated hemoglobin levels and kidney function parameters in streptozotocin-induced diabetic rats. These constituents were quantified using Soxhlet, liquid–liquid extraction (LLE), and high-performance liquid chromatography (HPLC)-diode array detecto (DAD). The outcomes exhibited a positive correlation between levels of coffee oil and diterpenes with a roasting degree. However, it demonstrated a negative correlation between caffeine and chlorogenic acid with a roasting degree. The male rats were categorized into two sections: healthy (nondiabetic) and streptozotocin-induced diabetic groups. Rats have daily administrated 2 ml of coffee extract using an oral gavage subjected to different roasting degrees for 3 weeks. Fasting blood glucose (FBG), urea, and creatinine in serum were assayed at baseline and end of the experiment. The highest significant elevation (Pa = 0.016) in the mean urea and creatinine levels was noted in the diabetic group administrated with dark coffee extract whereas the lowest elevation was in the diabetic group administrated with green coffee extract. In conclusion, our study has shown that coffee roasting degree may have a potential negative effect on kidney function that may accelerate or exacerbate diabetic nephropathy in induced diabetic rats. A noteworthy change in urea levels was observed in diabetic rats treated with dark-roasted coffee, which might be attributed to the decline in antioxidant constituents: chlorogenic acids and diterpenes.
Keywords: Nephropathy, coffee, quantification, diabetes, caffeine, chlorogenic acids